Relational influences on experiences with assisted dying: A scoping review. (November 2020) - Variath, Caroline; Peter, Elizabeth; Cranley, Lisa; Godkin, Dianne; Just, Danielle
Background: Family members and healthcare providers play an integral role in a person's assisted dying journey. Their own needs during the assisted dying journey are often, however, unrecognized and underrepresented in policies and guidelines. Circumstances under which people choose assisted dying, and relational contexts such as the sociopolitical environment, may influence the experiences of family members and healthcare providers. Ethical considerations: Ethics approval was not required to conduct this review. Aim: This scoping review aims to identify the relational influences on the experiences of family members and healthcare providers of adults who underwent assisted dying and of those unable to access assisted dying due to the loss of capacity to consent. Methods: A literature search was conducted in four databases, including MEDLINE, EMBASE, Cumulative Index to Nursing and Allied Health Literature (CINAHL) and PsycINFO. The search retrieved 12, 074 articles, a number narrowed down to 172 articles for full-text screening. Thirty-six articles met the established inclusion criteria. A feminist relational framework guided the data analysis. Results: Five key themes on the influences of family members' and healthcare providers' experiences throughout the assisted dying process were synthesized from the data. They include (1) relationships as central to beginning the process, (2) social and political influences on decision making, (3) complex roles and responsibilities of family members and healthcare providers, (4) a unique experience of death, and (5) varying experiences following death. Conclusion: The feminist relational lens, used to guide analysis, shed light on the effect of the sociopolitical influences and the relationships among patients, families, and healthcare providers on each other's experiences. Addressing the needs of the family members and healthcare providers is vital to improving the assisted dying process. Including families' and healthcare providers' needs within institutional policies and enhancing collaboration and communication among those involved could improve the overall experience.